1891 Nev. Stat. 78 - (:unkn) unknown (My University, 1891)
Ch. 67, § 1: If any person or persons . . . shall discharge any gun, pistol or any other fire arm at any train, car, locomotive or tender . . . or shall aid or abet or procure any of the above mentioned acts to be done or attempted shall be deemed guilty of a misdemeanor
Keywords: DISCHARGE